2022
DOI: 10.1088/1361-6668/ac5be9
|View full text |Cite
|
Sign up to set email alerts
|

High critical current solution derived YBa2Cu3O7 films grown on sapphire

Abstract: Superconducting fault current limiters are very attractive devices which require to increase its robustness against the destructive hot spots. The use of sapphire substrates to grow YBa2Cu3O7 films is a very attractive approach due to its high thermal conductivity. This article reports the growth of microcrack-free, epitaxial YBa2Cu3O7(CZO) (YBCO)/YSZ/r-cut layers by Chemical Solution Deposition (CSD)barely polished sapphire substrates on Ce1-xZrxO2which can be produced in long lengths at low cost. The surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The fundamental requisite for the scale-up and industrial appeal of these materials is the preparation of thick YBCO films with high performance. For this purpose, one of the crucial requirements in CSD is the need to develop a robust solution synthesis method compatible with spin coating and industrially scalable processes (slot die, inkjet printing) with the possibility to tune the concentration and rheology without compromising reproducibility, solution stability, and homogeneity, being the final thickness of the films directly correlated to solution rheology and the deposition method. , …”
Section: Resultsmentioning
confidence: 99%
“…The fundamental requisite for the scale-up and industrial appeal of these materials is the preparation of thick YBCO films with high performance. For this purpose, one of the crucial requirements in CSD is the need to develop a robust solution synthesis method compatible with spin coating and industrially scalable processes (slot die, inkjet printing) with the possibility to tune the concentration and rheology without compromising reproducibility, solution stability, and homogeneity, being the final thickness of the films directly correlated to solution rheology and the deposition method. , …”
Section: Resultsmentioning
confidence: 99%
“…The origin of this unique behavior of sapphire substrate remained obscure and it was generally associated to a strong difference in the thermal expansion of both phases (YBCO and sapphire). In a recent work, however, it was shown that the multilayer YBCO/CZO/YSZ/sapphire could be grown with thicknesses beyond 400 nm without crack formation and that, actually, the cracks appeared during the tetragonal-orthorhombic transition occurring during the oxygenation step [178]. A thorough analysis of the strain state of the different layers of this heterostructure showed that, while in the YBCO/CZO/YSZ multilayered structure the YBCO films keep a compressive state (no tendency to generate cracks) in the case of the sapphire substrate architecture the tetragonal YBCO films also keeps a compressive state but during the orthorhombic transition the decrease of the a-axis parameter is reduced versus the bulk value and so a tensile strain remains along this direction in the YBCO film and so a tendency to form cracks.…”
Section: Nucleation Growth and Oxygenation Of Pristine Rebco Films An...mentioning
confidence: 99%
“…The findings show that DEA has a positive effect on film growth and provide valuable information about the role of the chelating agents for the fabrication of high-quality YBCO films. The third article dealing with CSD-grown YBCO films is the one of Pop et al in which the authors focused on the difficult task of growing YBCO films on sapphire substrates [3]. The search of adequate substrates for every particular application is becoming more important since the experience with the use of certain devices brings new needs.…”
mentioning
confidence: 99%